Consumers Attitude and Intention Towards Online Purchasing - Siti Salwani, Meor Ahmad (2004)

(untitled)
Online shopping is one of buying methods, which has been accepted widely in the world. This method has started to win hearts of Malaysian consumers. Online shopping is online versions of physical retail stores where all transactions and their relevant activities take place in online cyber space. The general objective of the study is to examine the factors that influence consumer, especially Universiti Utara Malaysia (UUM) student’s intention to online shopping. While, the specific objectives of this study is to identify whether trust, quality and loyalty to website influence the student intention online shopping. 100 percent of questionnaires were accepted when 84 of questionnaire was distributed randomly to the students. Findings indicate quality and loyalty to website are significantly and positively related to intention to online purchase, contributing 26.8 percent (R2 = 0.268) and 6.1 percent (R2 = 0.061) variance in purchase intention.